PEMAHAMAN MASYARAKAT TERHADAP PENTINGNYA HUTAN DI LAHAN GAMBUT DI SEKITAR KAWASAN RIMBO PANJANG KABUPATEN KAMPAR PROVINSI RIAU - Lisman, Aprizal; M. Mardhiansyah, M. Mardhiansyah; Yoza, Defri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Peatland is one of natural resource that is very important and also in the economy of the country, including the availability of products in the form of forest timber and non-timber. Shrinking of the peatland area would provide the social, economic and health are devastating for the people of Indonesian. Example of the fires in peatlands not only cause economic losses but also has led to hundreds of thousands of residents suffered respiratory health problems that require careful management. RimboPanjang recent years becometalks of various parties, because peatland located in the area affected by fire due to forest clearing for agriculture and plantation. This study is a qualitative research and the method used was survey. The results showed the level of understanding of the importance of peatland forests for the environment in the village ofRimbo Panjang Kampar regency reached 83.15%, the public response quite well know the importance of peatland forests amounted to 68.42%.Keywords: Forest, peatlands, communityunderstanding